Quality of family planning services and associated factors among reproductive age women attending family planning unit at public health facilities in Dire Dawa, Eastern Ethiopia, 2021 - Legesse Abera; Ezira Ejigu; Mickiale Hailu; Daniel Tadesse; Abdu Omer (BMC, 2023)
Abstract Introduction Improving the quality of care has been a necessary goal for family planning programs worldwide. Even though extensive work has been done, the contraceptive prevalence rate is still low (41% in Ethiopia, 30.5% in Dire Dawa) and the unmet need for contraception is high (26%) in Ethiopia. Moreover, quality of care in family planning services has an important role in increasing coverage of services and program sustainability. Therefore, the objective of this study was to assess quality of family planning services and associated factors among reproductive age women attending family planning unit in public health facilities in Dire Dawa, Eastern Ethiopia. Methods A facility-based cross-sectional study was conducted among reproductive-age women attending a family planning unit in Dire Dawa, Eastern Ethiopia, from September 1-30/2021. A total of 576 clients were selected by systematic random sampling and interviewed using a pre-tested structured questionnaire. SPSS version 24 was used to analyze the data, which included descriptive statistics, bi-variable and multivariable logistic regression analyses. To determine the presence of an association between dependent and independent variables, AOR, P-value 0.05, and 95% CI were used. Results A total of 576 clients participated in the study and provided a response rate of 99%. The overall satisfaction of clients with FP services was 79%[95% CI:75.2%, 82.9%]. Having primary education (AOR = 2.11, 95% CI(1.11-4.24), convenient facility opening hours (AOR = 3.13, 95% CI (2.12-5.75), maintaining privacy (AOR = 4.1, 95% CI(2.50-8.12), demonstrating how to use F/P method (AOR = 1.98, 95% CI (1.01-5.20), and discussing F/P issues with husbands (AOR = 5.05, 95% CI: 3.33-7.64) were positively significantly associated with client satisfaction. Conclusion and recommendation This study revealed that about four-fifth of the clients was satisfied with the service they received. Clients' education, facility opening hour, maintained privacy, discussion with husband, and demonstration of how to use the methods were associated with client satisfaction. Therefore, health facility heads should improve facility opening hour. Health care providers should maintain client privacy every time, and should consistently utilize information, education, and communication materials during consultation sessions by giving more attention to client who has no education. Partner's discussion on family planning issues should also be encouraged.